Preparing the Research Paper - Dangle, Lorraine F. (Fairfield CEBCO Standard Publishing, 1963)
This book will help to effectively use information, once it has been gathered. A procedure for preparing to write a research paper is described. The writer should be able to apply this procedure for any paper.
Keywords: Writing